2016
DOI: 10.1186/s13072-016-0074-4
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation signature of human fetal alcohol spectrum disorder

Abstract: BackgroundPrenatal alcohol exposure is the leading preventable cause of behavioral and cognitive deficits, which may affect between 2 and 5 % of children in North America. While the underlying mechanisms of alcohol’s effects on development remain relatively unknown, emerging evidence implicates epigenetic mechanisms in mediating the range of symptoms observed in children with fetal alcohol spectrum disorder (FASD). Thus, we investigated the effects of prenatal alcohol exposure on genome-wide DNA methylation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
130
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(138 citation statements)
references
References 80 publications
4
130
0
Order By: Relevance
“…Additionally, emerging evidence of epigenetic changes due to prenatal alcohol exposure has been reported [57]. For example, distinct DNA methylation patterns observed in adolescents and children with FASD [73] may effect immune organ development and immune-related gene expressions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, emerging evidence of epigenetic changes due to prenatal alcohol exposure has been reported [57]. For example, distinct DNA methylation patterns observed in adolescents and children with FASD [73] may effect immune organ development and immune-related gene expressions.…”
Section: Discussionmentioning
confidence: 99%
“…Though it remains to be demonstrated that reduced γ-Pcdh protein levels are causal for any of the dendritic or synaptic defects seen in DS, the phenotypes observed in Pcdhg null cortex (as discussed above, decreased dendrite arborization and altered dendritic spine number and morphology) are certainly consistent with such a possibility [54,82]. Studies exploring methylation patterns in FASD similarly discovered increased methylation of the clustered Pcdhs both in the brains of FASD mouse models and in buccal cells of human FASD patients [168,169]. …”
Section: Roles In Behavior and Neurological Or Neurodevelopmental Dismentioning
confidence: 99%
“…Also, lentiviral knockdown of MeCP2 normalized the decreases in Pomc and normalized the aberrant hormonal response to stress in fetal alcohol-exposed animals (Gangisetty, Bekdash, Maglakelidze, & Sarkar, 2014). Finally, DNA methylation is also differentially altered in human populations exposed to in utero alcohol, as a recent study of methylation status of buccal swabs from children with FASD showed hypermethylation in genes implicated in neurodevelopment and neurological diseases such as anxiety, epilepsy, and autism-spectrum disorders (Portales-Casamar et al, 2016). …”
Section: Epigenetic Effects Of Alcohol Exposure On Somatic Cellsmentioning
confidence: 99%